Pengaruh Alat Peraga Mobil-Mobilan Terhadap Minat Belajar Matematika Siswa SMPN I Bola - Agustina Luju; Wahyuningsih Wahyuningsih; Magdalena Dhema; Muhamad Epi Rusdin (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2020)
Teaching aids in the world of education is a medium that mediates to help clarifying concepts in learning mathematics. This study aims to determine the efect of the use of toy car props on students’ interest in learning mathematics, especially in comparison material. This research was conducted at SMPN I Bola VII class semester 2 of the 2019/2020 scholl year. This type of research is quantitative by using a quasi-experimental methods. The population of this study were 192 studentsof class VII SMPN I Bola with a sample 0f 23 students in the experimental class and 23 from the control class. The sampling technique used is class random technique. The instrument used in this study was a questionnaire of interest in learning. Before carrying out a hypothesis test it is necessary to do a prerequisite test that is a test for normality and homogeneit. The normality test obtained significant values in the experimental class and control were 0,136 and 0,620, because the value obtained has a significance level 0f >0,05, it can be stated that the data is normally distributed. For the homogeneity test, the results obtained a significant value of 0,001 at a sisnificant level of 0,05, so it can be said that the data is homogeneous. After the data is normally distributed and homogeneous, it is continued with hypothesis testing. Hypothesis testing used the independent sample t-test obtained value of t-count > t-table where t-count = 6,49 while t-table = 2,01 which means that the use of toy props has an effect on the interest in learning mathematics in class VII SMPN I Bola where students’interest in learning mathematics increases. Thus the teacher can use toy props related to the material and can be used in matematics learning so that students’ interest in learning mathematics increases.